Pengembangan Sistem Kontrol Kecepatan Pengelasan (Welding Velocity) Smaw Berbasis Microcontroller Arduino Uno - Purnawan, Trio; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Welding is an important part of industrial growth because it plays a major role in engineering and production repair. Shield metal arc welding (SMAW) is a welding technique using an electric current that forms an arc of current and a webbed electrode. In the SMAW welding process, there are variables that determine the quality of the welding results, including the selection of electrodes, the selection of currents in the machine that must be adjusted, and the position and welding speed that must be precise. In welding, high speeds can cause less penetration, reduce joint strength and result in less heat input. Welding speed that is too high will affect the narrow bead shape and low bead reinforcement. In addition, it can change the mechanical properties of the weld area in the form of increased tensile strength and low elongation. From these problems, this research will make a speed control system for a stepper motor that drives a welding handlebar, a speed controller based on a microcontroller. Keywords : SMAW, speed controller, microcontroller